SINAES: as diferentes faces da avaliação na UFRN - Eussen, Shirmenia Kaline da Silva Nunes (2010)
This thesis entitled SINAES: the different faces of the evaluation at UFRN, aims to analyze the configuration that the national policy for assessment in higher education has taken on UFRN. We assume that in recent years there are an oscillation between the concepts of evaluation, according with the logic of public administration it has preferred an approach that presents itself as a promoter of quality, sometimes with regulatory aspects, sometimes with educational ones. The text discusses the use of the new assessment tools for higher education placing them under the new demands on state reform context in which this is to promote and measure quality based on the values of excellence and competitiveness. This movement arises from the redefinition of the role of the State that has been taking features of Evaluator State. From a historical review of government initiatives in the field of evaluation, we analyze the characteristics of assessment policies outlined over the past decades. We are based on the theoretical method that aims to examine the multiple determinants that shape a particular reality from the larger movement of totality. To identify, in this case, connections and ruptures that have emerged over the history of assessment policies aimed at higher education by checking their determinants in order to better explain the reality. To investigate the object of this study we used as instruments: the research literature and research documents, the semi-structured interviews and non-participant observation. The study revealed that there are different practices of evaluation and that before to establishment the SINAES program, the UFRN already had a culture of an institutional assessment, more participatory and democratic, opposing to the rigidity of the self-assessment in SINAES program that it was instituted by the Commission for assessment (CPA). We also noticed that the implementation of the SINAES at URFN has been performed very slowly and the breadth and complexity of the evaluation process has contributed to hinder its implementation in all dimensions provided by MEC. Although it was observed that in its operationalization the SINAES has assumed a more normative assessment and directed to establish rankings between courses and higher education schools than to establish a more qualitative assessment in this system. As regards the evaluation of the undergraduate course studied on this research and subjected to the three dimensions of evaluation proposed by SINAES (self-assessment, Evaluation of Courses and ENADE) it was not possible to verify an effective integration between the methods of assessing conducted. The results are considered separately, in only a partial view of the course evaluated the proposal what pits the SINAES as a system that involves the totality